European Financial Cross-Border Consolidation: At the crossroads in Europe? By exception, evolution or revolution? - Jean-Paul Abraham; Peter van Dijcke (SUERF - The European Money and Finance Forum, 2002)
In the context of the New Economics of Banking, the study analyses crossborder financial consolidation from the point of view of bank strategies. The main hypothesis of the work is that, in the present decade, the Pan-European landscape of the financial sector will be determined by what is happening in a limited number of banks, this number being rather arbitrarily fixed at 100. The basic issue to be clarified is not whether a second round of cross-border mergers and acquisitions will occur after the present pause; but how it will occur: according to an ' evolution' or a ' revolution' scenario. In the study, the sample comprises the 100 largest banking groups in Europe, selected on the basis of the Bankscope data. This sample is supposed to be composed of subgroups with similar characteristics, which can be discovered by statistical analysis, using clustering techniques. The clusters help identify peer groups. Particularly interesting for the study are the cases where banks want to overcome the constraints of a domestic market, which, in the perspective of European integration, no longer suffices to satisfy their ambitions and the competition rules of the national and European authorities. After a general discussion of motives, driving forces and discouraging factors in cross-border financial consolidation, the study concentrates on four topics, mostly discussed within the same conceptual and statistical framework: (i) a factual analysis of the M&A activity of the late Nineties and the first years of the present decade, where cross-border deals were overshadowed by domestic transactions; (ii) a presentation, via self-organising maps, of the European banking panorama in the year 2000 and of the panorama changes in the period 1995- 2000. The clusters in this panorama feature at the same time national and comparative advantage aspects. In the clusters of high efficiency British and Nordic Banks predominate. In the clusters of higher vulnerability German and some Italian banks are prominent; (iii) a discussion of the track record of 29 European banking groups, divided into three groups according to their M&A activity (domestic M&A, cross-border M&A, steady state without much M&A). On the average, the performance of the domestic M&A reference group is stronger than the results of the other groups; (iv) a more detailed discussion of four cases, all of them belonging to the crossborder M&A reference group: ABN-AMRO, ING and FORTIS in the Benelux area, NORDEA in Scandinavia. The origin of the consolidation differentiates the three Benelux cases from the Scandinavian one: necessity to overcome the limitations of the national domestic market in a perspective of growth on the one hand, new perspectives in the aftermath of the Scandinavian banking crisis of the early Nineties on the other. On the basis of the preceding analysis, the answer to the basic issue favours the ' evolution' scenario,where the cross-border M&A activity remains a gradual enlargement of and a complement to the domestic market activity, but with an increasing weight of cross-border deals, when large banks become more sensitive to the limitations of their own national domestic market. In this way Europe would gradually and partly become the enlarged home market of the national champions and their challengers.
Keywords: G15; G21; G34; 330; Financial consolidation; cross-border M&A; European and global financial integration; Internationale Bank; Bank; Übernahme; Branchenentwicklung; Benelux-Staaten; Nordeuropa